2017
DOI: 10.21276/aimdr.2017.3.2.ot1
|View full text |Cite
|
Sign up to set email alerts
|

Central Macular Thickness in Diabetic Retinopathy- A Comparative Study

Abstract: Background: Macular oedema is one of the important signs in patients with diabetic retinopathy which progresses to complete blindness. Therefore, early diagnosis of the disease can prevent the progression of disease. Methods: This comparative study was conducted on 200 eyes of 100 diabetics and non-diabetics each. Subjects were divided into five groups according to the International Clinical Diabetic Retinopathy Disease Severity Scale. In each stage, macula was assessed for the presence or absence of Clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Numerous attempts have been undertaken to develop a test that predicts DR ( Gartaganis et al., 2001 ; Ivers et al., 2001 ; Safi et al., 2018 ). With the advancement of diagnostic tools, clinicians observed that patients with DR exhibit changes in neuroretinal structure especially the thickness of the macula even before the appearance of microvascular lesions ( Carpineto et al., 2016 ; Abrar et al., 2017 ). However, some studies did not find any significant alteration in macular structure between diabetic subjects and healthy individuals ( Biallosterski et al., 2007 ; Massin et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous attempts have been undertaken to develop a test that predicts DR ( Gartaganis et al., 2001 ; Ivers et al., 2001 ; Safi et al., 2018 ). With the advancement of diagnostic tools, clinicians observed that patients with DR exhibit changes in neuroretinal structure especially the thickness of the macula even before the appearance of microvascular lesions ( Carpineto et al., 2016 ; Abrar et al., 2017 ). However, some studies did not find any significant alteration in macular structure between diabetic subjects and healthy individuals ( Biallosterski et al., 2007 ; Massin et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in keeping with previous studies. 1,5,[14][15][16] which have reported similar results. Mean± SD hemoglobin A1c was noted as 9.78±3.31.…”
Section: Table-iii Frequency Of Severity Of Diabetic Retinopathymentioning
confidence: 56%
“…16 The findings are supported by previous studies. Abrar et al 5 our study subjects this may be because of bad glycemic control in our diabetic population. It is stated that the retinal capillary become leaky and lipid exudates accumulates within the layers of retina causing macular edema and increased CMT.…”
Section: Discussionmentioning
confidence: 82%
“…16 The findings are supported by previous studies. Abrar et al 5 reported CMT of 291.0±63.0 µm in diabetic retinopathy. Results of present study show the CMT was very high in our study subjects this may be because of bad glycemic control in our diabetic population.…”
Section: Table-iii Frequency Of Severity Of Diabetic Retinopathymentioning
confidence: 97%
“…Early diagnosis and intervention may halt the disease process and prevention of blindness. 5 Glycemic control and timely intervention must be initiated to prevent complications of DR and postpones the disease process and potential visual compromise. Approximately 10% diabetics are suffering from ME.…”
Section: Introductionmentioning
confidence: 99%